2022
DOI: 10.3390/ijerph19042104
|View full text |Cite
|
Sign up to set email alerts
|

Does Entrepreneurs’ Military Experience Promote Corporate Environmental Investment? Evidence from Chinese Private Firms

Abstract: Although it is well established that the military experience of top executives has a profound influence on firms’ decisions, empirical evidence on how military experience matters to corporate environmental investment has been scarce. Drawn on imprinting theory and upper echelon theory, this study examines the impact of entrepreneurs’ military experience on corporate environmental investment. Using a nationwide survey of Chinese private firms, we find that entrepreneurs’ military experience significantly promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Second, this paper enriches the growing literature on the determinants of corporate environmental policy. Recent studies have found several factors that may affect corporate D&O insurance and environmental investment environmental responsibility, including institutional shareholders (Kim et al, 2019;Chen et al, 2020), top executives' experience (Hong et al, 2022) and firm-level characteristic (Abeysekera and Fernando, 2020;Li et al, 2020;Tian et al, 2021). We document that D&O insurance significantly affects firms' environmental investment, adding to this stream of literature to some extent.…”
supporting
confidence: 50%
See 3 more Smart Citations
“…Second, this paper enriches the growing literature on the determinants of corporate environmental policy. Recent studies have found several factors that may affect corporate D&O insurance and environmental investment environmental responsibility, including institutional shareholders (Kim et al, 2019;Chen et al, 2020), top executives' experience (Hong et al, 2022) and firm-level characteristic (Abeysekera and Fernando, 2020;Li et al, 2020;Tian et al, 2021). We document that D&O insurance significantly affects firms' environmental investment, adding to this stream of literature to some extent.…”
supporting
confidence: 50%
“…Some research examines the effects of factors such as firm-level characteristics and the external environment on environmental investment. For example, it's found the level of environmental investment is higher in cross-shareholding firms (Tian et al, 2021) and firms whose top executives have military experience (Hong et al, 2022). But firms invest less in environmental projects when local officials under high pressure of economic growth target relax environmental regulation intensity (Zhong et al, 2022).…”
Section: The Determinants Of Corporate Environmental Responsibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…According to upper echelons theory, it has been found that corporate behavior relies to some extent on managers' subjective decision deployment [6,7]. Based on a cognitive structure perspective, heterogeneous characteristics of executives map out differentiated green value preferences, which in turn influence corporate green innovation decisions and behaviors [8]. However, the existing studies are one-sided in that they only look at the heterogeneous characteristics of executives from the perspective of cognitive structure to inspire green innovation.…”
Section: Introductionmentioning
confidence: 99%